Civil aviation radial tire corrugated protective layer glue and preparation method thereof

The corrugated protective layer rubber prepared through a specific ratio and process solves the problem of insufficient mechanical properties and adhesion properties of the corrugated protective layer rubber in the existing technology, improves the durability and resistance to foreign object puncture of civil aviation radial tires, and reduces production costs.

CN120737448AActive Publication Date: 2025-10-03T RUBBER
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511213645.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-10-03
Estimated Expiration
2045-08-28

AI Technical Summary

Technical Problem

The mechanical properties and adhesive properties of existing corrugated protective layer rubber are insufficient to meet the harsh high-speed and high-load operating conditions of civil aviation radial tires.

Method used

1# smoked rubber is used as the main material, and auxiliary materials such as N330 carbon black, N46 engine oil, insoluble sulfur, anti-reversion agent HVA-2, adhesive RS, C9 resin and tackifying resin HT-M are added. Through specific process steps, a corrugated protective layer adhesive with high adhesion, impact resistance, tear resistance, puncture resistance and fatigue resistance is prepared.

Benefits of technology

The adhesive performance and comprehensive performance of the corrugated protective layer adhesive are improved, the production cost is reduced, and the durability and resistance to foreign object puncture of the tire are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a civil aviation radial tire corrugated protective layer rubber and a preparation method thereof, and the rubber adopts a technical method that 1 # smoked sheet rubber is used as a main body material, N330 carbon black is used as a reinforcing system, N46 engine oil is used as a plasticizer, insoluble sulfur, an accelerant DZ and the like are used as vulcanizing agents, and an adhesive RS, C9 resin and tackifying resin HT-M are used as an adhesive system. The rubber material with high adhesion, impact resistance, tear resistance, puncture resistance, low heat generation and good fatigue resistance is prepared through a certain mixing process, and the rubber material serving as the corrugated protective layer rubber material of the civil aviation radial tire has good adhesion performance of a framework material (aramid fiber rope), higher physical performance, lower heat generation performance and good anti-fatigue performance. The damage resistance of foreign object puncture resistance and mechanical damage resistance of the civil aviation radial tire is improved, so that the durability of the tire is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber processing and production, in particular to a high-performance civil aviation radial tire corrugated protective layer rubber and a preparation method thereof. Background Art

[0002] The corrugated protective layer is a special component of civil aviation radial tires. It uses special skeleton materials, fixed number and spacing of roots side by side, and is coated with glue on the upper and lower surfaces with a certain amplitude and wavelength. It is calendered by special equipment to form a semi-finished rubber component with a fixed thickness.

[0003] The corrugated protective layer is on the outside of the annular cylindrical belt layer, tightening the belt layer group, absorbing and bearing the upward stress of the tire caused by expansion when inflated to internal pressure, reducing deformation, effectively improving the uniformity of stress distribution on the belt layer, reducing the stress at the edge of the belt layer, and eliminating the phenomenon of belt edge delamination; at the same time, it significantly improves the cut resistance of the tire body, and inhibits the occurrence, development and circumferential expansion of tread damage, improves the tread's resistance to foreign object puncture and mechanical damage, increases the durability of the tire, and thus improves the overall performance of the civil aviation radial tire.

[0004] The corrugated protective layer is made of aramid cord. Based on its operating conditions and characteristics, the corrugated protective layer rubber must have high adhesion, impact resistance, tear resistance, puncture resistance, low heat generation, good fatigue resistance, and process performance. It is designed to meet the demanding high-speed and high-load operating conditions of civil aviation radial tires. Summary of the Invention

[0005] The present invention aims to address the deficiencies in mechanical properties and adhesive properties of existing corrugated protective layer rubber materials and to provide a corrugated protective layer rubber for civil aviation radial tires and a preparation method thereof. The rubber material is made of 1# smoked sheet rubber as a main material, and N330 carbon black, N46 engine oil, insoluble sulfur, anti-reversion agent HVA-2, adhesive RS, C9 resin, tackifying resin HT-M, etc. are added as main auxiliary materials. The rubber material is prepared according to a certain ratio and dosage through a certain process. The rubber material has the effects of high adhesion, impact resistance, tear resistance, puncture resistance, good fatigue resistance, and good comprehensive performance.

[0006] In order to achieve the above objectives, the present invention adopts the following technical solutions: A method for preparing a corrugated protective layer adhesive for a civil aviation radial tire, wherein the names and mass ratios of the components of the protective layer adhesive are as follows: 100 parts of 1# smoked rubber, 5-10 parts of zinc oxide, 2-6 parts of stearic acid, 1.0-2.0 parts of antioxidant RD, 1-3 parts of antioxidant 4020, 3-5 parts of N46 engine oil, 3-5 parts of insoluble sulfur HDOT-20, 0.5-1.0 parts of accelerator DZ, 0.2-1.0 parts of anti-reversion agent HVA-2, 0.1-0.5 parts of scorch retarder CTP, 30-50 parts of N330 carbon black, 1-5 parts of adhesive RS, and 1-5 parts of resin mixture; The resin mixture is prepared by adding C9 resin and tackifying resin HT-M in a mass ratio of 3:2 into a sand mill and grinding them finely. The particle size of the resin mixture is 2 to 3 microns. The preparation method of the corrugated protective layer adhesive for a civil aviation radial tire comprises the following specific steps: (1) Preparation of resin mixture: C9 resin and tackifying resin HT-M were added to a sand mill according to the mass ratio and ground. The continuous grinding method was used. The feed pressure was 1.4 MPa to 1.9 MPa, the grinding medium filling amount was 35% to 55%, and the grinding time was 10 to 30 minutes to obtain a resin mixture with a particle size of 2 to 3 μm. (2) plasticizing the 1# tobacco sheet rubber in an internal mixer at a plasticizing speed of 30-50 rpm, a wind pressure of 0.5-0.6 MPa, and a rubber discharge temperature of 160-170° C. to obtain plasticized rubber; (3) The prepared plasticized rubber, zinc oxide, stearic acid, antioxidant RD, antioxidant 4020, adhesive RS and resin mixture are added into an internal mixer according to the mass ratio for a stage of rubber mixing. The mixing speed is 30-50 rpm and the wind pressure is 0.5-0.6 MPa. When the mixing is continued for 35-45 seconds and the temperature is 60-65°C, 1 / 3-2 / 3 of the required amount of N330 carbon black is added. When the mixing is continued for 85-95 seconds and the temperature is 90-95°C, N46 engine oil is added. When the mixing is continued for 115-125 seconds and the temperature is 120-1 When the temperature reaches 25°C, the remaining N330 carbon black is added, and the mixing is continued for 145-155 seconds. When the temperature reaches 140-145°C, the top bolt is lifted and lowered once. When the mixing is continued for 185-215 seconds and the temperature reaches 150-155°C, the mixing temperature in the internal mixer is lowered to 130-135°C by spraying liquid nitrogen. The mixing is continued for 275-300 seconds, and the binder is discharged at a temperature of 160-165°C. The discharged rubber is placed in an open mixer, the rubber thickness is 2mm, and the roller is wrapped. The left and right 3 / 4 rubber is tapped 3 times each. The lower sheet is cooled for 8h-24h to obtain a first-stage mixed rubber. (4) The prepared first-stage mixed rubber, insoluble sulfur HDOT-20, anti-scorch agent CTP, accelerator DZ, and anti-reversion agent HVA-2 were added into an internal mixer according to the mass ratio for second-stage mixing. The rotation speed was 15-25 rpm, the air pressure was 0.4-0.5 MPa, and the top bolt was raised and lowered twice between 40 and 90 seconds. The mixing was continued for 180-190 seconds and the rubber was discharged at a temperature of 100-105°C. The discharged rubber was placed in an open mixer. The rubber thickness was 2 mm and the roller was wrapped. The left and right 3 / 4 rubber was cut 3 times each. The sheet was cooled to obtain the corrugated protective layer rubber.

[0007] In step (1), the grinding medium of the sand mill is one of ceramic balls, carbon steel balls, stainless steel balls, high chromium cast iron balls or corundum balls.

[0008] The present invention provides a corrugated protective layer rubber for civil aviation radial tires and a preparation method thereof. The corrugated protective layer rubber utilizes 1# smoked sheet rubber as the raw rubber system. Its main component is polyisoprene, an unsaturated rubber that is easy to blend, process, and vulcanize. The vulcanized rubber can crystallize in an oriented manner under stress, producing a self-reinforcing effect. The rubber exhibits excellent mechanical properties, with a tensile strength of up to 30 MPa. Natural rubber also exhibits excellent tear resistance, damage resistance, durability, and flex resistance, making it a preferred rubber matrix material for the preparation of high-performance civil aviation radial tires. N330 carbon black, a typical furnace-processed carbon black with a normal vulcanization rate and an average particle size range of 26 to 30 nm, is used as the reinforcement system. N46 engine oil, a lubricating softener for natural rubber and general-purpose synthetic rubber, exhibits excellent process performance. Insoluble sulfur HDOT-20 is used as a vulcanizing agent. It is insoluble in rubber and is evenly dispersed in the rubber mix. It does not spray onto the surface during cooling and storage. After vulcanization, it imparts excellent physical and mechanical properties to the vulcanized rubber. The bonding system uses adhesive RS, C9 resin, and tackifying resin HT-M, which provide the formula with good adhesion to aramid cord.

[0009] Compared with the prior art, the present invention has the following beneficial effects: 1. The corrugated protective layer rubber for civil aviation radial tires prepared by the present invention has the characteristics of high adhesion, impact resistance, tear resistance, puncture resistance, low heat generation, fatigue resistance and easy processing, and improves the physical and mechanical properties of the rubber material, especially the bonding performance with aramid cords; 2. The main raw materials of the corrugated protective layer rubber of the civil aviation radial tire prepared by the present invention, namely 1# smoked rubber, N330 carbon black, N46 engine oil and insoluble sulfur HDOT-20, have a stable supply and low price, thereby reducing the production cost of the civil aviation radial tire. DETAILED DESCRIPTION

[0010] The present invention is further described below with reference to the following examples, but is not intended to limit the present invention.

[0011] Examples 1-3 The corrugated protective layer rubber for civil aviation radial tires prepared in Examples 1-3 was prepared by mixing the following materials and amounts in parts by weight (see Table 1) in an internal mixer through multiple stages. The specific preparation process is as follows: (1) Preparation of resin mixture: C9 resin (particle size range 0.1-5 mm) and tackifying resin HT-M (particle size range 0.4-0.6 mm) were added into a sand mill in a mass ratio of 3 / 2 for fine grinding. The continuous grinding method was used. The feed pressure was 1.8 MPa, the filling amount of ceramic balls (particle size 5.0 mm) as grinding media was 45%, and the grinding time was 20 min. The resin mixture was obtained. The particle size of the resin mixture was 2-3 μm. (2) Add the 1# cigarette rubber required by the formula into an internal mixer for plasticization at a mixing speed of 40 rpm, an air pressure of 0.5-0.6 MPa, a rubber inlet temperature of 70°C, and a rubber discharge temperature of 165°C to obtain plasticized rubber.

[0012] (3) Add the prepared plasticized rubber, zinc oxide, stearic acid, antioxidant RD, antioxidant 4020, adhesive RS, and resin mixture into the internal mixer according to the mass ratio for a stage of rubber mixing. The mixing speed is 40 rpm, the wind pressure is 0.5-0.6 MPa, and the rubber inlet temperature is 70 ° C. When the mixing is continued for 40 seconds and the temperature is 65 ° C, add 1 / 2 of the required N330 carbon black. When the mixing is continued for 90 seconds and the temperature is 95 ° C, add the required N46 engine oil. Continue mixing for 120 seconds and the temperature is 125 ° C. Add the remaining N330 carbon black, mix for 145 seconds and the temperature reaches 145°C, lift the top plug, drop the top plug at 155 seconds, continue mixing for 185 seconds, when the temperature reaches 155°C, lower the mixing temperature in the internal mixer by spraying liquid nitrogen, stop cooling at 215 seconds, drop the temperature to 135°C, continue mixing for 300 seconds and discharge the rubber, the discharge temperature is 165°C, place the discharged rubber in an open mixer, the rubber thickness is 2mm, wrap the roller, tap the left and right 3 / 4 for 3 times each, cool the lower sheet for 15 hours, and obtain a section of mixed rubber.

[0013] (4) The prepared first-stage mixed rubber, insoluble sulfur HDOT-20, anti-scorch agent CTP, accelerator DZ, and anti-reversion agent HVA-2 were added into the internal mixer according to the mass ratio for second-stage mixing. The speed was 20 rpm, the air pressure was 0.4-0.5 MPa, and the temperature of the rubber feed was 70°C. The top bolt was raised and lowered twice at the 40th and 90th seconds of mixing, respectively. The rubber was mixed for 180 seconds and discharged at a temperature of 100°C. The discharged rubber was placed in an open mixer. The thickness of the rubber was 2 mm and the roller was wrapped. The left and right 3 / 4 rubbers were cut 3 times each. The rubber was cooled to obtain the corrugated protective layer rubber.

[0014] The physical property parameters of the corrugated protective layer adhesive prepared in Examples 1-3 are shown in Table 2.

[0015] Table 1 Amounts of various raw materials used in the tire corrugated protective layer rubber formulations in Examples 1-3 and Comparative Examples 1-5 (parts by mass) Raw material name Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 1# Smoked rubber 100 100 100 100 100 zinc oxide 5 10 8 5 4 stearic acid 2 4 6 2 1 Antioxidant RD 1 2 1.5 1 1 Antioxidant 4020 1 2 1.3 1 1 N46 engine oil 3 5 4 3 3 Insoluble sulfur HDOT-20 3 5 4 3 3 Accelerator DZ 0.5 0.8 1.0 0.5 0.5 Anti-reversion agent HVA-2 0.5 0.8 1.0 0.5 0.5 Anti-scorch agent CTP 0.1 0.3 0.2 0.1 0.1 N330 30 40 50 30 30 Adhesive RS 1 3.5 5 1 0.5 Resin mixture 1 5 3 / 0.5 Gu Malong / / / 1 /

[0016] Comparative Example 1 The formula of the corrugated protective layer adhesive for civil aviation radial tires in Comparative Example 1 differs from that in Example 1 in that the resin mixture in Example 1 is replaced with the same mass fraction of coumarone resin. The other components and proportions in the formula are the same as in Example 1, and the preparation process is the same as in Example 1. The physical property parameters of the prepared protective layer adhesive are shown in Table 2.

[0017] Comparative Example 2 The formula of the corrugated protective layer adhesive for civil aviation radial tires in Comparative Example 2 differs from the formula in Example 1 in that the mass fractions of zinc oxide, stearic acid, adhesive RS, and resin mixture in the formula are different from those in Example 1. The other components and proportions in the formula are the same as those in Example 1, and the preparation process is the same as that in Example 1. The physical property parameters of the prepared protective layer adhesive are shown in Table 2.

[0018] Comparative Example 3 1. The formula of the corrugated protective layer of the civil aviation radial tire in Comparative Example 3 is the same as that of Example 2. 2. The preparation of the resin mixture in step (1) during the preparation process is different from that in Example 2. The other preparation processes and parameters are the same as those in Example 2. The physical property parameters of the protective layer adhesive prepared are shown in Table 2. Step (1) Preparation of a resin mixture: C9 resin and tackifying resin HT-M are conventionally mixed in a mass ratio of 3 / 2 to obtain a resin mixture. The particle size of the resin mixture is 0.1 to 5 mm. The remaining process is the same as in Example 2.

[0019] Comparative Example 4 1. The formula of the corrugated protective layer of the civil aviation radial tire in Comparative Example 4 is the same as that of Example 2. 2. The mixing process of the first stage of the mixed rubber in the preparation process is different from that in Example 2. The specific preparation method is as follows: (1) Preparation of a resin mixture: C9 resin (particle size range 0.1-5 mm) and tackifying resin HT-M (particle size range 0.4-0.6 mm) were added to a sand mill in a mass ratio of 3 / 2 for fine grinding. A continuous grinding method was used with a feed pressure of 1.8 MPa, a grinding medium ceramic ball (particle size 5.0 mm) filling amount of 45%, and a grinding time of 20 min to obtain a resin mixture with a particle size of 2-3 μm. (2) Add the required No. 1 tobacco sheet rubber into an internal mixer for plasticization at a mixing speed of 40 rpm, an air pressure of 0.5-0.6 MPa, a rubber feed temperature of 70°C, and a rubber discharge temperature of 165°C to obtain plasticized rubber; (3) The prepared plasticized rubber, zinc oxide, stearic acid, antioxidant RD, antioxidant 4020, adhesive RS, and resin mixture are added to an internal mixer according to the mass ratio for one-stage rubber mixing. The mixing speed is 40 rpm, the air pressure is 0.5-0.6 MPa, and the rubber feeding temperature is 70°C. When the mixing is continued for 40 seconds and the temperature is 65°C, 1 / 2 of the required N330 carbon black is added. When the mixing is continued for 90 seconds and the temperature is 95°C, the required N46 engine oil is added. When the mixing is continued for 120 seconds and the temperature is 125°C, the remaining N330 carbon black is added. When the mixing is continued for 145 seconds and the temperature reaches 145°C, the top bolt is lifted and the top bolt is lowered at 155 seconds. The mixing is continued for 210 seconds and the rubber is discharged. The discharge temperature is 165°C. The discharged rubber is placed in an open mixer. The rubber thickness is 2 mm and the roller is wrapped. The left and right 3 / 4 rubber is tapped 3 times each. The sheet is cooled for 15 hours to obtain a first-stage rubber mix. (4) The prepared first-stage mixed rubber, insoluble sulfur HDOT-20, anti-scorch agent CTP, accelerator DZ, and anti-reversion agent HVA-2 were added to an internal mixer according to the mass ratio for second-stage mixing. The speed was 20 rpm, the air pressure was 0.4-0.5 MPa, and the feeding temperature was 70°C. The top bolt was raised and lowered twice at the 40th and 90th seconds of mixing, respectively. The mixing was continued for 180 seconds and the rubber was discharged at a temperature of 100°C. The discharged rubber was placed in an open mixer. The rubber thickness was 2 mm and the left and right 3 / 4 rubbers were cut 3 times each. The rubber was cooled and the corrugated protective layer rubber was obtained. The physical properties of the prepared protective layer rubber are shown in Table 2.

[0020] Comparative Example 5 1. The formula of the corrugated protective layer of the civil aviation radial tire in Comparative Example 5 is the same as that of Example 2. 2. The mixing time and the binder removal temperature during the preparation process are different from those in Example 2. The specific preparation method is as follows: (1) Preparation of a resin mixture: C9 resin (particle size range 0.1-5 mm) and tackifying resin HT-M (particle size range 0.4-0.6 mm) were added to a sand mill in a mass ratio of 3 / 2 for fine grinding. A continuous grinding method was used with a feed pressure of 1.8 MPa, a grinding medium ceramic ball (particle size 5.0 mm) filling amount of 45%, and a grinding time of 20 min to obtain a resin mixture with a particle size of 2-3 μm. (2) Add the required No. 1 tobacco sheet rubber into an internal mixer for plasticization at a mixing speed of 40 rpm, an air pressure of 0.5-0.6 MPa, a rubber feed temperature of 60°C, and a rubber discharge temperature of 155°C to obtain plasticized rubber; (3) The prepared plasticized rubber, zinc oxide, stearic acid, antioxidant RD, antioxidant 4020, adhesive RS, and resin mixture are added into an internal mixer according to the mass ratio for a stage of rubber mixing. The mixing speed is 40 rpm, the wind pressure is 0.5-0.6 MPa, and the rubber feeding temperature is 60°C. When the mixing is continued for 30 seconds and the temperature is 55°C, 1 / 2 of the required N330 carbon black is added. When the mixing is continued for 80 seconds and the temperature is 85°C, the required N46 engine oil is added. When the mixing is continued for 110 seconds and the temperature is 115°C, the remaining The remaining N330 carbon black was mixed for 135 seconds and the temperature reached 135°C. The top bolt was raised and lowered after 145 seconds. The mixing temperature in the internal mixer was reduced by spraying liquid nitrogen when the temperature reached 145°C. The temperature was stopped at 205 seconds and the temperature was reduced to 125°C. The mixing temperature was continued until the binder was discharged at 290 seconds. The discharge temperature was 155°C. The discharged rubber was placed in an open mixer with a thickness of 2mm and rolled. The left and right 3 / 4 rubbers were tapped 3 times each. The rubber was cooled for 15 hours to obtain a first-stage mixed rubber. (4) The prepared first-stage mixed rubber, insoluble sulfur HDOT-20, anti-scorch agent CTP, accelerator DZ, and anti-reversion agent HVA-2 were added into an internal mixer according to the mass ratio for second-stage mixing. The speed was 20 rpm, the air pressure was 0.4-0.5 MPa, and the rubber inlet temperature was 60°C. The top bolt was lifted and lowered twice at the 30th and 80th seconds of mixing, and the rubber was discharged at 170 seconds. The discharge temperature was 90°C. The discharged rubber was placed in an open mixer. The rubber thickness was 2 mm and the roller was wrapped. The left and right 3 / 4 rubbers were cut 3 times each. The sheet was cooled to obtain a corrugated protective layer rubber. The physical properties of the prepared protective layer rubber are shown in Table 2.

[0021] The physical properties of the rubber materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested. The results are shown in Table 2. Table 2 Physical properties of the rubber compounds obtained in Examples 1-3 and Comparative Examples 1-5 pilot projects Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Tensile strength, MPa 25.0 26.3 24.6 20.9 20.5 21.1 18.1 17.3 300% modulus of elongation, MPa 11.3 11.6 11.2 10.1 9.8 9.2 8.0 9.9 Elongation at break, % 492 506 482 454 467 432 428 436 Hardness, Shore A 70 74 75 70 69 73 74 74 Permanent deformation, % 34 32 30 35 35 33 31 33 <![CDATA[Specific gravity, g / cm 3 > 1.125 1.128 1.135 1.125 1.125 1.128 1.128 1.128 Compression heat, ℃ 23.1 23.8 27.0 41.2 42.5 43.0 44.5 43.3 H extraction, N 210.3 227.6 223.2 89.6 90.2 70.4 132.6 150.3

[0022] It can be seen from the above table that, compared with Example 1, the same mass fraction of coumarone resin is used in Comparative Example 1 to replace the resin mixture in Example 1, and the H extraction, tensile strength, 300% tensile stress and elongation at break of the final rubber are significantly reduced, and the compression heat generation is increased. The bonding system of adhesive RS, C9 resin and tackifying resin HT-M used in the present application not only improves the adhesion of the rubber, but also promotes the comprehensive performance of the rubber through mutual promotion with other auxiliary materials; after adjusting the mass fractions of zinc oxide, stearic acid, adhesive RS and resin mixture in Comparative Example 2, the tensile strength, 300% tensile stress, H extraction and elongation at break of the final rubber are significantly reduced, and the compression heat generation is increased. Compared with Example 2, in Comparative Example 3, C9 resin and tackifying resin HT-M were conventionally mixed in a mass ratio of 3 / 2 to obtain a resin mixture; from the test results, the H extraction, tensile strength, 300% modulus, and elongation at break of Example 2 were improved, and the compression heat generation was reduced, indicating that after the C9 resin and the tackifying resin HT-M were ground in a mass ratio of 3 / 2, the particle size was smaller, and it was easier to disperse evenly in the rubber compound, less likely to agglomerate, and could more tightly fill the gaps in the rubber compound, thereby improving the performance of the rubber compound; compared with Example 2, Comparative Example 4 removed the liquid nitrogen spraying method during the preparation process. From the test results, the H extraction, tensile strength, 300% modulus, and elongation at break of Example 2 were improved, and the compression heat generation was reduced, indicating that adding the liquid nitrogen spraying method during the mixing process of the rubber compound and reducing the mixing temperature in the internal mixer can help extend the mixing time of the rubber compound, resulting in a more sufficient and uniform mixing effect, which can improve the performance of the rubber compound. Compared to Example 2, Comparative Example 5 used different mixing and dumping temperatures during the preparation process, resulting in a corresponding decrease in the overall performance of the final rubber compound. A reasonable dumping temperature can improve the performance of the rubber compound. In summary, compared to Comparative Examples 1-5, Examples 1-3 showed significant improvements in H extraction test values, including increased tensile strength, 300% modulus, and elongation at break, and lower heat generation, demonstrating that the present invention exhibits superior high adhesion, impact resistance, tear resistance, puncture resistance, low heat generation, and good fatigue resistance.

[0023] The tensile strength, 300% modulus of tensile stress, elongation at break and permanent deformation are tested in accordance with GB / T528-2009 "Rubber, vulcanized or thermoplastic rubber - Test method for tensile stress-strain properties"; the hardness is tested in accordance with GB / T531.1-2008 "Rubber, vulcanized or thermoplastic rubber - Test method for indentation hardness - Part 1: Shore durometer method (Shore hardness)"; the specific gravity is tested in accordance with GB / T533-2008 "Rubber, vulcanized or thermoplastic rubber - Determination of density"; the compression heat generation is tested in accordance with GB / T1687.3-2016 "Rubber, vulcanized - Determination of temperature rise and fatigue resistance in flexure test - Part 3: Compression flexure test (constant strain)"; the H withdrawal test is tested in accordance with GB / T2942-2009 "Rubber, vulcanized to fiber cord - Determination of static bond strength - H withdrawal method".

[0024] Table 3 Manufacturers' brands of raw materials used in Examples 1-3 and Comparative Examples 1-5 raw material factory 1# Smoked rubber Indonesia zinc oxide Dalian Zinc Oxide Plant stearic acid Wilmar Oils & Fats Technology Co., Ltd. Antioxidant RD Kemai Chemical Co., Ltd. Antioxidant 4020 Sennics Technology Co., Ltd. N46 engine oil Shenyang Tianhong Lubricant Co., Ltd. Insoluble sulfur HDOT-20 Shandong Shangshun Chemical Co., Ltd. Accelerator DZ Kemai Chemical Co., Ltd. Anti-reversion agent HVA-2 Zhejiang Huangyan Zhedong Rubber Additives Co., Ltd. Anti-scorch agent CTP Haicheng Haiteng Additives Co., Ltd. N330 carbon black Anshan Jianlong Carbon Black Co., Ltd. Adhesive RS Wuxi Huasheng Rubber New Materials Technology Co., Ltd. C9 resin Shandong Qilong Chemical Co., Ltd. Tackifying resin HT-M Shandong Yanggu Huatai Chemical Co., Ltd. Gu Malong Anshan Yihua Chemical Co., Ltd.

Claims

1. A method for preparing a corrugated protective layer rubber for a civil aviation radial tire, characterized in that: The protective layer adhesive is made of the following raw materials in the following mass ratios: 100 parts of 1# smoked rubber, 5-10 parts of zinc oxide, 2-6 parts of stearic acid, 1.0-2.0 parts of antioxidant RD, 1-3 parts of antioxidant 4020, 3-5 parts of N46 engine oil, 3-5 parts of insoluble sulfur HDOT-20, 0.5-1.0 parts of accelerator DZ, 0.2-1.0 parts of anti-reversion agent HVA-2, 0.1-0.5 parts of scorch retarder CTP, 30-50 parts of N330 carbon black, 1-5 parts of adhesive RS, and 1-5 parts of resin mixture; The resin mixture is prepared by adding C9 resin and tackifying resin HT-M in a mass ratio of 3:2 into a sand mill and grinding them finely. The particle size of the resin mixture is 2 to 3 microns. The preparation method of the corrugated protective layer adhesive is as follows: (1) Preparation of resin mixture: C9 resin and tackifying resin HT-M were added to a sand mill according to the mass ratio and ground. The continuous grinding method was used. The feed pressure was 1.4 MPa to 1.9 MPa, the grinding medium filling amount was 35% to 55%, and the grinding time was 10 to 30 min. The resin mixture was obtained and the particle size reached 2 to 3 μm. (2) Plasticizing the 1# tobacco sheet rubber in an internal mixer at a plasticizing speed of 30-50 rpm, an air pressure of 0.5-0.6 MPa, and a rubber discharge temperature of 160-170°C to obtain plasticized rubber; (3) Add the prepared plasticized rubber, zinc oxide, stearic acid, antioxidant RD, antioxidant 4020, adhesive RS, and resin mixture according to the mass ratio into the internal mixer for mixing. The mixing speed is 30-50 rpm and the air pressure is 0.5-0.

6. MPa, add 1 / 3-2 / 3 of the required N330 carbon black when the mixing time is 35-45 seconds and the temperature is 60-65℃, continue mixing for 85-95 seconds and the temperature is 90-95℃, add N46 engine oil, continue mixing for 115-125 seconds and the temperature is 120-125℃, add the remaining N330 carbon black, mix for 145-155 seconds and the temperature is 140-145℃, lift and drop the top bolt once, mix for 185-215 seconds and the temperature is 150-155℃, reduce the mixing temperature in the internal mixer to 130-135℃ by liquid nitrogen spraying, continue mixing for 275-300 seconds and discharge the glue, the discharge temperature is 160-165℃, the discharged rubber is placed in the open mill, the rubber thickness is 2 mm, the left and right 3 / 4 rubber is tapped 3 times each, and the lower sheet is cooled for 8-24 h, to prepare a rubber mix; (4) The first-stage mixed rubber, insoluble sulfur HDOT-20, anti-scorch agent CTP, accelerator DZ, and anti-reversion agent HVA-2 are added to the internal mixer according to the mass ratio for second-stage mixing. The speed is 15-25 rpm, the air pressure is 0.4-0.5 MPa, and the top bolt is raised and lowered twice between 40 and 90 seconds. The mixing is continued for 180-190 seconds and the rubber is discharged at a temperature of 100-105 °C. The discharged rubber is placed in an open mixer. The thickness of the rubber is 2 mm and the roller is wrapped. The left and right 3 / 4 rubber is cut 3 times each. The sheet is cooled to obtain the corrugated protective layer rubber.

2. The method for preparing the corrugated protective layer adhesive for civil aviation radial tires according to claim 1, characterized in that: In step (1), the grinding medium of the sand mill is ceramic balls, carbon steel balls, stainless steel balls, high chromium cast iron balls or corundum balls.

3. A corrugated protective layer adhesive for a civil aviation radial tire prepared according to the preparation method of claim 1 or 2.

Citation Information

Patent Citations

  • All-steel radial tire shoulder wedge and preparation method thereof

    CN110452425A

  • Aviation radial tire belted layer protective layer hanging rubber and preparation method thereof

    CN114854104A

  • Rubber composition for tire and pneumatic tire using the same

    JP2021070778A